Analisis kemampuan pemodelan matematika melalui konteks produksi pempek ditinjau dari self-efficacy - Suryati Suryati; Dwi Astuti; Akhmad Fajari; Uzair Uzair; Nila Kesumawati; Allen Marga Retta (IKIP Siliwangi, 2026)
Research on ethnomathematics has generally emphasized the use of cultural contexts. The present study aims to analyze students’ mathematical modeling ability based on self-efficacy levels through the ethnomathematics context of pempek production. This study employs a mixed-methods approach with a sequential explanatory design involving 36 tenth-grade students of SMKN 1 Buay Madang. Data were collected through self-efficacy questionnaires, mathematical modeling tests, and semi-structured interviews, and were analyzed using descriptive quantitative analysis and Miles & Huberman’s qualitative model, then integrated at the interpretation stage. The findings indicate a tendency for differences in mathematical modeling ability based on self-efficacy levels, where students with higher self-efficacy tend to demonstrate more complete modeling processes. Furthermore, the pempek production context in this study is understood as a contextual situation that helps students connect mathematical problems with real-life situations, rather than as an evaluation of the effectiveness of an instructional intervention. These findings highlight the importance of integrating self-efficacy and ethnomathematical contexts in vocational mathematics education.